Plasma volume treated with double filtration plasmapheresis and outcomes of acute antibody-mediated rejection in kidney transplant recipients: A retrospective cohort study - Kajohnsak Noppakun (2020)
© 2020 International Society for Apheresis, Japanese Society for Apheresis, and Japanese Society for Dialysis Therapy A retrospective cohort study was conducted to evaluate the association between the plasma volume treated by double filtration plasmapheresis and allograft outcomes for the treatment of acute antibody-mediated rejection in kidney transplant recipients. Patients were divided into two groups: group 1, plasma volume treated between 1 and <1.3 total plasma volume and group 2, plasma volume treated ≥1.3 total plasma volume. Primary outcome was ≥50% reduction of serum creatinine rising from baseline value at 1 month. A total of 32 courses (146 sessions) of double filtration plasmapheresis were performed; 17 and 15 courses in group 1 and group 2, respectively. Primary outcome occurred in 41% of group 1 and 40% of group 2 (adjusted risk ratio 1.15 [95%CI, 0.48-2.76]). Graft loss at 1 year did not differ between the two groups (adjusted hazard ratio 0.65 [95%CI, 0.23-1.87]). Infection tendency seemed to be higher in group 2 (40% vs 18%, P =.243).